Gerakan Sehat Bersama: Pemeriksaan Gula Darah Untuk Menunjang 9 Pilar Transformasi Kesehatan - Digna Renny Panduwati; Suryani M. F Situmeang; Nita Andriani Lubis; Sri Widia Ningsih; Wardati Humaira (Universitas Negeri Gorontalo, 2024)
Diabetes is a chronic disease characterized by high body sugar levels, but the body does not utilize them. Based on data from 2023, 14% of Indonesia's population has diabetes. The spread of diabetes also penetrates rural areas, posing a threat to rural areas and threatening the health of rural communities, and Saentis Village is no exception. The program